PENGARUH PENERAPAN PEMBELAJARAN AKTIF TEKNIK QUIZ TEAM DISERTAI BAHAN AJAR TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII MTsN LUBUK SIKAPING TAHUN PELAJARAN 2012/2013 - Ayunda, Febrisa Putri; Mulyati, Mulyati; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRACTThis research is background by the low of outcomes student in biology class VIII of MTsN Lubuk Sikaping and haver minimal competencess of criterion (KKM) yet. The out comes of student are lowered by the teacher make of interesting teaching methods yet. This research intend how the influence of the aplication active learning Quiz Team technical and teaching material for the study outcomes of students is biology at class VIII of MTsN Lubuk Sikaping in periode 2012/2013. This kind of research is an eksperimental which using of the Randomized Control Group postest only design, the populations are all of student at class VIII of MTsN Lubuk SikapingÂ  in periode of 2012/2013. The sampling by purposive sampling technical a sample he found by class VIII2 as eksperimental class and class VIII3 as control class. The instrument are make is written test in objective question. The data of analysis technical used uji ât by level Î± 0,05. The outcomes of data analysisÂ  is found a price t hitung 6,18, while t table 1,66. This is t arithmatic > t table. Therefore hiphotesis is accepted that the application ofÂ  active learning quiz team technical and teaching material can improve the outcomes of student at class VIII of MTsN Lubuk Sikaping in the study periode 2012/2013.Â Â